A novel PARAFAC model for continental hot springs reveals unique dissolved organic carbon compositions. (March 2020) - Nye, Joshua J.; Shock, Everett L.; Hartnett, Hilairy E.
Highlights: DOC concentration and fluorescent DOM composition vary with pH of hot springs. Hot spring DOM composition is significantly different from surface water DOM. PARAFAC modeling shows a fluorescent component unique to highly acidic hot springs. Abstract: Dissolved organic carbon in hot springs reflects a range of sources and biogeochemical processes. We evaluated ~200 continental hot spring samples, with a range in pH and temperature, collected from the Tengchong hydrothermal region, Yunnan Province, China and Yellowstone National Park, Wyoming, USA. Dissolved organic carbon concentrations ranged from 16.7 µM to 2.97 mM. Acidic springs displayed the highest values and widest range in carbon concentration. Alkaline springs had a narrower range and lower average concentrations. Carbon composition was evaluated using ultraviolet absorption and 3D-fluorescence spectroscopy. Total fluorescence was correlated (p < 0.05) with dissolved organic carbon (DOC) concentration. Fluorescence excitation-emission matrices were deconvolved using parallel factor analysis. We validated a five-component model that represented >97% of the total fluorescence. Our model includes three humic-like components, one protein-like component, and one novel component exclusively observed in highly acidic springs. The closest spectral match to the novel component is an acid-soluble lignin produced during high-temperature, acid digestion of wood pulp. Humic-like components were dominant in mid-pH springs (4 < pH < 7) indicating these springs had greater terrestrial carbon input. Acidic springs also exhibited evidence for terrestrial carbon input. Alkaline springs, in contrast, consistently had low dissolved organic carbon content and low fluorescence intensity suggesting that these springs had little terrestrial input. This absence of terrestrial carbon implies a predominantly hydrothermal fluid source. A comparison of the traditional fluorescence indices with our five model components suggest that these indices may have limited utility in continental hot springs with multiple organic matter sources and alteration processes.